TP53 Co-Mutations in Advanced EGFR-Mutated Non–Small Cell Lung Cancer: Prognosis and Therapeutic Strategy for Cancer Therapy - Liu, Surui; Yu, Jin; Zhang, Hui; Liu, Jie (Frontiers in Oncology, 2022)
Lung cancer is the leading cause of cancer-related deaths worldwide. As the most prevalent molecular mutation subtypes in non-small cell lung cancer (NSCLC), EGFR-TKIs are currently a standard first-line therapy for targeting the mutated EGFR in advanced NSCLC patients. However, 20-30% of this subset of patients shows primary resistance to EGFR-TKIs. Patients with co-mutations of EGFR and several other genes have a poor response to EGFR-TKIs, whereas the prognostic and predictive significance of EGFR/TP53 co-mutation in NSCLC patients remains controversial. Meanwhile, little is known about how to choose an optimal therapeutic strategy for this subset of patients. Presently, no drugs targeting TP53 mutations are available on the market, and some p53 protein activators are in the early stage of clinical trials. A combination of EGFR-TKIs with antiangiogenic agents or chemotherapy or other agents might be a more appropriate strategy to tackle the problem. In this review, we describe the prognostic and predictive value of EGFR/TP53 co-mutation in NSCLC patients, investigate the mechanisms of this co-mutation affecting the response to EGFR-TKIs, and further explore optimal regimens effectively to prolong the survival time of the NSCLC patients harboring this co-mutation.